Legal framework of cooperative surplus in the Portuguese legal system: Some issues - Meira, Deolinda (Cooperativismo & Desarrollo, 2025)
This study analyses the main vectors of the legal regime governing cooperative surplus in Portugal. It refers to a positive economic result arising from the pursuit of the cooperative’s mutual purpose, and therefore excludes results generated from transactions with third parties. The cooperative surplus corresponds to the difference between the income and the costs of cooperative activities. Its distribution as cooperative refunds does not occur automatically but depends on a general meeting resolution to that effect. A percentage of the surplus for the financial year goes into the legal reserve and the education, training, and information reserve. Portuguese legislation does not allow the cooperative refunds if there are losses from previous financial years, nor does it set any obligation to return surpluses.
Keywords: surplus; cooperative refunds; mutual purpose; third- party operations